Phosphorus Enrichment Affects Immobilization but not Litter Decomposition or Exoenzymatic Activities in a Pampean Stream - Ferreiro, Nicolas Andres (2011)
The effect of phosphorous enrichment on decomposition rate, exoenzymatic activities (β-glucosidase, cellobiohydrolase and alkaline phosphatase), and macroinvertebrate abundance in Typha latifolia leaves were assessed in a 2nd order Pampean stream (Central Argentina). Phosphorous was added to a downstream reach while another reach located upstream was kept intact and, once significant differences in phosphorus concentration in water were attained, leaf bags were attached to each reach bottom. T. latifolia leaves lost 77% of their initial weight along 154 days and decomposition rates were not significantly different between reaches. Besides, neither exoenzymatic activities nor macroinvertebrate abundances differed between reaches. However, an increment in leaf phosphorus content, attributed to immobilization by decomposer microorganisms, was detected in the enriched reach.